Sifilis Pada Kehamilan - Darmawan, Hari; Purwoko, Izazi Hari; Devi, Mutia (Fakultas Kedokteran Universitas Sriwijaya, 2020)
Syphilis is a sexually transmitted infection caused by bacterium Treponema pallidum which can be transmitted through sexual intercourse, blood transfusion, and vertically from mother to fetus. If pregnant woman suffers from syphilis, transplacental infection can occur to the fetus, causing abortion, prematurity, low birth weight, stillbirth, or congenital syphilis. The diagnosis of syphilis in pregnancy is established based on history, clinical manifestations, laboratory and serologic examination. Screening in the first trimester with non-treponema tests such as rapid plasma reagin (RPR) or venereal disease research laboratory (VDRL) combined with a treponema test such as the treponema pallidum hemagglutination assay (TPHA) is important for every pregnant woman. Clinical manifestations of syphilis to the fetus depend by gestational age and stage of maternal syphilis also fetal immune response. Early detection and adequate management are important to prevent the transmission of syphilis infection from mother to fetus.